Design and usability evaluation of a mobile‐based‐self‐management application for caregivers of children with severe burns. - Toolaroud, Parissa Bagheri; Nabovati, Ehsan; Mobayen, Mohammadreza; Akbari, Hossein; Feizkhah, Alireza; Farrahi, Razieh; Jeddi, Fatemeh Rangraz (International Wound Journal, 2023)
Paediatric burns are a major public health issue because of long‐term physical, psychological and social consequences and the high cost of treatment. The aim of this study was to design and evaluate a mobile‐based self‐management application for caregivers of children with severe burns. A participatory design technique was employed to develop the Burn application, which included three main phases: the determination of application requirements, the design and evaluation of the low‐fidelity prototype, and the design and evaluation of the high‐fidelity prototypes. In the first phase, application requirements were determined via validated paper questionnaires using the Delphi technique. In the second step, a low‐fidelity prototype was prepared using conceptual models and evaluated through a focus group with specialists. Seven specialists reviewed the application and evaluated how this prototype meets functional requirements and objectives. The third phase was performed in three stages. First, the high‐fidelity prototype was designed and developed by the JAVA programming language. Second, a cognitive walk‐through was carried out to show how users can interact with the mobile application and how it works. Third, this program was installed on the mobile phones of 28 caregivers of burned children, eight IT experts, and two general surgeries, and the prototype's usability was evaluated. In the present study, most caregivers of children with burns stated that after discharge, they face problems regarding infection control and wound care (4.07) and how to perform physical activity (4.12). User registration, educational materials, caregiver‐clinician communication, chat box, and appointment booking, safe login were the most important characteristic of the Burn application. Mean usability evaluation scores were in the range of 7.92 ± 0.238 to 8.10 ± 0.103, which is considered at a "good" level. From the Burn program design experience, it can be concluded that co‐design with health care specialists can significantly support and meet the specialists' and patients' needs and ensure the program's usefulness. In addition, application evaluation by users involved and not involved in the application design process can help enhance usability.